2010
DOI: 10.1021/jp911905p
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Catalyst Size and Metal−Carbon Interactions on the Growth of Single-Walled Carbon Nanotubes

Abstract: Single-walled carbon nanotubes grow by decomposition of a carbon-containing precursor gas over metal nanocatalysts. It is known that the shape, size, and chemical nature of the catalysts play significant roles in the nucleation and growth processes. Here, we use reactive molecular dynamics simulations to analyze how the catalyst particle size and the strength of adhesion between the surface and nascent carbon structures may affect the growth process. As a result, we determine if the process leads to cap lift-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…This correction depends on the number of carbon atoms around the perimeter of the cap, which is proportional to d. On a per carbon atom basis, this correction is proportional to d −1 since the number of carbon atoms in the cap is proportional to d 2 . On the basis of previous reports, 45,47,48 these corrections may be on the same order of magnitude as the strain energy.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…This correction depends on the number of carbon atoms around the perimeter of the cap, which is proportional to d. On a per carbon atom basis, this correction is proportional to d −1 since the number of carbon atoms in the cap is proportional to d 2 . On the basis of previous reports, 45,47,48 these corrections may be on the same order of magnitude as the strain energy.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…This hypothesis is further supported by DFT results obtained by Bolton's group [131][132] as well as recent MD calculations of Yakobson's group. [133][134] The latter showed that the catalyst particle either grows a SWCNT or gets encapsulated, depending on an interplay of the curvature energy and the work of adhesion of carbon to the metal particle. In the early stages of the reaction, as the carbon cap forms, the curvature energy plays a decisive role.…”
Section: Growth Mechanism Of Swcntsmentioning
confidence: 99%
“…The system with a CNT attached to a pure Ni cluster was found to be energetically favored compared with a system containing the same CNT attached to nickel carbide. Burgos et al [43] used reactive MD simulations to analyze how the catalyst particle size and the strength of adhesion between the surface and the nascent carbon structures may affect the growth process. The MD simulations results illustrated that the work of adhesion must be weak enough so that the curvature energy of a spherical fullerene is less favorable than that of a SWCNT with the same diameter, to allow the cap-lifting process to take place.…”
Section: Discrete Computational Modelingmentioning
confidence: 99%
“…The salient feature of this approach is that it directly gives the total energy and local adhesion energy of the system. Burgos et al [43,44] used the most suitable potentials for different types of interactions involved, in their simulations. By this, the realistic modeling of the most important interactions in the synthesis process was possible, which provided a close insight over reaction pathways and at the nucleation and the initial stages of growth.…”
Section: Discrete Modelsmentioning
confidence: 99%